Infection of Anaplasma phagocytophilum and Ehrlichia spp. in Opossums and Dogs in Campeche, Mexico: The Role of Tick Infestation - Rojero-Vázquez, Edgar; Gordillo-Pérez, Guadalupe; Weber, Manuel (Frontiers in Ecology and Evolution, 2017)
In recent years, some tick-borne diseases such as anaplasmosis and ehrlichiosis became widespread worldwide, threatening the health of humans, domestic animals and wildlife. The aims of this study were to determine the presence of Anaplasma phagocytophilum, Ehrlichia canis and Ehrlichia chaffeensis in 102 opossums (Didelphis spp.) and 44 owned free-ranging dogs in southeastern Mexico using a specific polymerase chain reaction (PCR). Anaplasma phagocytophilum was detected in opossums and dogs with a prevalence of 3 and 27 %, respectively. E. canis was only present in 7 % of dogs, while we didn’t detect E. chaffeensis in any host. We report the first evidence of infections of Anaplasma phagocytophilum in Didelphis virginiana and D. marsupialis in México. The infection rates and patterns we found of A. phagocytophilum suggest that dogs are more directly involved in the ecology of this pathogen than opossums. Despite the small prevalence found, our results are of public health concern because of the zoonotic capabilities of A. phagocytophilum, the high tick infestation rates found and because both opossums and free-ranging dogs can achieve high population densities in the region.